Stress Granules Modulate SYK to Cause Tau-Associated Neurocognitive Deterioration in 5XFAD Mouse After Anesthesia and Surgery - Shen, Yang; Zhang, Tong; Zhang, Yinglin; Wang, Yinuo; Yao, Junyan (Frontiers in Aging Neuroscience, 2021)
Background Alzheimer’s disease (AD) is the most common type of dementia. However, no curative therapy has been found effective to slow down the process of AD. It is reported that anesthesia and surgery will induce neurocognitive deterioration in AD, but the mechanism is not quite clear. In this study, we aim to compare the cognitive impairment between 5XFAD transgenic (Tg) mice and its littermate (LM) after isoflurane anesthesia and surgery to clarify the specific impacts of anesthesia and surgery on individuals with AD and to explore the mechanisms. Methods We performed abdominal surgery in cognitively impaired, 4-month-old female 5XFAD mice and LM control mice. Isoflurane anesthesia (1.4%) was induced and maintained over 2 h. Open field and fear conditioning tests were conducted on 1, 3 and 7 days after anesthesia and surgery. The total distance, velocity and freezing time were the major outcomes. P-tau (AT8), tau oligomers (T22), stress granules (SGs), the SYK tyrosine kinase and p-SYK in the hippocampus at postoperative day 1 were evaluated by Western Blot assays. The colocalization of SGs, SYK, p-SYK, and neurons in the hippocampus section was assessed using qualitative immunofluorescence. Results In the open field test, no difference between the distance moved and the velocity of LM mice and 5XFAD Tg mice were found on day 1 after anesthesia and surgery. 5XFAD Tg mice exhibited reduced freezing time of fear conditioning context test on postoperative day 3, but not on day 7; the LM mice showed no changes in FCTs. Furthermore, p-tau, tau oligomers, SGs, SYK and p-SYK were evident in the hippocampus region of 5XFAD Tg mice on a postoperative day 1. In addition, SGs, SYK, p-SYK were colocalized with hippocampus neurons, as shown by immunofluorescence. Conclusion This study demonstrates that anesthesia and surgery may induce tau-associated neurocognitive deterioration in individuals with AD. The mechanism under it may be associated with SGs and the tyrosine kinase, SYK. After anesthesia and surgery, in 5XFAD Tg mice, SGs were formed and SYK was phosphorylated, which may contribute to the phosphorylation of tau protein. This study provided hints that individuals with AD may be more vulnerable to anesthesia and surgery.